(untitled) (Asia Pacific Journal of Social Innovation, 2024)
Upon the request from Iligan City Traffic Management Office (TCTMO), a study is conducted to ease the traffic congestion along Roxas Avenue, from Quezon Avenue to Consunji Street intersections, Iligan City. The request is in line with the Memorandum of Agreement (MOA) on Academe LGU Linkage in Urban Transport between the City Government of Iligan and MSU Iligan Institute of Technology (MSU-IIT). Road inventory and intersection traffic volume counts are conducted in the study area to determine the extent of the problem. Other traffic managenment measures, such as travel time, travel delay, etc., are not included in the survey due to time and financial constraints. The results show that the average volumecapacity ratio in the study area is 0.50, which falls within the zone of stable flow. The percentage of vehicles that are right turning from Quezon Avenue to Roxas Avenue and from Roxas Avenue to Zamora Street exceeds 7% of the through traffic. Business establishments and vendors encroach the sidewalk areas. Traffic violations are rampant. Recommendations are presented to alleviate traffic congestion.